Observation of structural change-driven Griffiths to non-Griffiths-like phase transformation in Pr2-xSrxCoFeO6 (x = 0 to 1) - Pal A.; Anand K.; Kumar D.; Joshi A.G.; Yen P.T.-W.; Huang S.-M.; Yang H.D.; Ghosh A.K.; Chatterjee S. (My University, 2025)
The study of crystal structure, electronic structure, transport, and magnetic properties of heterovalent Sr2+ doped Pr2-xSrxCoFeO6 (x = 0.0 to 1.0) system have been done. Crystal structure study reveals an occurrence of structural change from orthorhombic (Pnma) to tetragonal (I4/m) phase above x = 0.6. A sudden transformation of the Griffiths-like to non-Griffiths-like magnetic phase is observed as the system changes its crystal structure from Pnma to I4/m. The X-ray photoemission spectroscopy (XPS) study suggests for the existence of mixed oxidation states of the B-site ions viz., Co3+/Co4+ and Fe3+/Fe4+, and it also indicates an increase in the mean oxidation states owing to the hole substitution (Sr2+). The temperature variation of the electrical resistivity of the studied systems follows two different transport mechanisms, such as the variable range hopping (VRH) (in the lower temperature region) and small polaron hoping (SPH) (in the higher temperature region) models. Dc magnetization study shows that a local competing ferromagnetic (FM) exchange interaction increases with Sr doping. Finally, the ac susceptibility study reveals breaking of the long-range-ordering in the system x = 1.0, which appears to be related to the structural change and enhanced spin frustration due to increased competing local FM exchange interactions. In addition, electronic density of states (DOS) calculations of PrSrCoFeO6 (i.e. x = 1.0) using the density functional theory (DFT) have been performed for various Co/Fe atomic distributions. For most of the Co/Fe atomic distributions studied, the calculations show that the total energy of the system with FM coupling among spins has slightly lower energy than that for antiferromagnetic (AFM) coupling. © 2022